Evaluation of STEM-Based Physics Learning on Students' Critical Thinking Skills: A Systematic Literature Review - Winarti; Dwi Sulisworo; Narentheren Kaliappen (Indonesian Review of Physics (IRiP), 2021)
This article discusses the importance of STEM learning in optimizing critical thinking skills in physics learning. It presents an overview of STEM learning to identify, train and improve students' critical thinking skills to assess misconceptions in the science education research literature since 2010. This study published articles in primary science education journals and indexed them in the leading research database to obtain data on STEM-based physics learning and critical thinking skills. To identify relevant studies in the literature, we conducted a systematic search of the two databases with the document analysis method. The investigation was limited to Indonesia's studies published between 2010 and 2020 for the most recent STEM-based physics learning studies and critical thinking skills based on the most recent findings. This study summarizes STEM learning at the high school and the undergraduate students. The implementation of the research related to STEM-based physics learning with critical thinking skills variables was in various teaching materials, learning models, and learning media. Teachers taught physics concepts using the STEM approach to improve critical thinking skills, including optical tools, thermodynamics, temperature and heat, dynamic fluids, and sound waves. The findings of this study can be used as a reference in the development of STEM learning patterns in the realm of science and physics education to improve students' critical thinking skills, which are the demands of skills in the 21st century that students must possess.